2009
DOI: 10.1038/sj.bjc.6605299
|View full text |Cite
|
Sign up to set email alerts
|

DKC1 overexpression associated with prostate cancer progression

Abstract: BACKGROUND: Dyskerin encoded by the DKC1 gene is a predominantly nucleolar protein essential for the formation of pseudouridine in RNA and the telomerase RNA subunit hTR. Inherited mutations inactivating dyskerin cause dyskeratosis congenita, a syndrome with progeroid features characterised by skin defects and haematopoiesis failure, as well as cancer susceptibility. In this study, we report DKC1 overexpression in prostate cancers. METHODS: Expression of DKC1 was measured by quantitative RT -PCR in prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 20 publications
11
100
0
Order By: Relevance
“…Past studies suggest that elevated dyskerin expression levels correlate with more aggressive disease (2,3,6); however, before the current investigation, there was a paucity of functional evidence supporting the significance of dyskerin expression levels in any cancer type, and no previous report of dyskerin suppression inhibiting tumor growth in vivo. The current study not only identifies DKC1 expression as a powerful independent prognostic indicator of poor clinical outcome, but also shows that high DKC1 expression has functional significance and potential as a therapeutic target in the MYC-driven malignancy neuroblastoma.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Past studies suggest that elevated dyskerin expression levels correlate with more aggressive disease (2,3,6); however, before the current investigation, there was a paucity of functional evidence supporting the significance of dyskerin expression levels in any cancer type, and no previous report of dyskerin suppression inhibiting tumor growth in vivo. The current study not only identifies DKC1 expression as a powerful independent prognostic indicator of poor clinical outcome, but also shows that high DKC1 expression has functional significance and potential as a therapeutic target in the MYC-driven malignancy neuroblastoma.…”
Section: Discussionmentioning
confidence: 64%
“…Subsequent studies demonstrated high DKC1 expression in various adult cancers, with the DKC1 promoter shown to be a target of c-Myc in breast cancer (2)(3)(4). Gene expression array and proteomic studies identified DKC1 among the suite of genes upregulated in neuroblastoma in association with MYCN amplification (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Dyskeratosis congenita patients have a nonsense mutation within DKC1, leading to diminished expression of Dyskerin accompanied by downregulation of telomerase activity. 45 Overexpression of DKC1 has been seen in solid tumors, and the silencing of DKC1 can reduce telomerase activity and rRNA pseudouridylation. 46,47 These findings suggest that the level of Dyskerin expression parallels the activation and inactivation of telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in tumor samples of human malignant melanoma, Nop58 is upregulated specifically in metastatic group compared to the non-metastatic group (69). For dyskerin, although downregulation of the expression has been observed in a subset of tumors (70), upregulated expression was determined in a number of human cancer cells and also its overexpression is correlated with aggressive proliferation of the tumor cells such as hepatocellular (71), colon (72), prostate (73,74), head and neck carcinomas (75). Given that the both Nop58 and dyskerin are unstable proteins and associated/stabilized by R2TP (16,17,76), the expression level of R2TP components also might be upregulated to maintain the target proteins level in above-mentioned cancers.…”
Section: Potential Role Of R2tp In Tumorigenesis Through Snornp Pathwaymentioning
confidence: 99%